Understanding the factors affecting the quantity and composition of street litter: Implication for management practices. Issue 3 (March 2023) - Rossi, Alessandra; Wu, Meiyin; Wolde, Bernabas T.; Zerbe, Kevin W.; David Hsu, Tsung-Ta; Giudicelli, Ariane; Da Silva, Rosana
Abstract: Some urban areas have more litter than others. Understanding the reason for this is important not only for dealing with urban littering but also for marine water quality because approximately 80% of the world's marine litter originates on land. This study aimed to better understand the quality and quantity of litter on sidewalks along with the sampling site's socio-economic attributes to better discern why some areas have more/different litter than others and what, if any, are the implications for a more tailored waste management strategy. We surveyed twice each of the 35 sites we selected from the Lower Passaic River watershed and the related Harbor Estuary within New Jersey, U.S.A. A total of 28, 431 litter items were recorded with a total mass and volume of 245.8 kg and 4.7 m 3, respectively. Floatable items accounted for 66% of all objects collected. Cigarette butts were the most numerous among all items (28%) and represented 43% of the total floatable items, the remaining 57% being represented by potentially recyclable items such as plastic, rubber, and Styrofoam. Stepwise linear regression was used to explore the relationship between the litter collected and various predictors. Among others, the results suggest the importance of strategically placing collection bins around properties with relatively lower assessed values, outdoor smoking areas, close to schools, and places where people predominantly walk to their destination. Possible management strategies include prohibiting single use plastic bags, limiting foam food ware, public education, and outreach.